Obraz nauki i naukowca w aspekcie kulturowo-cywilizacyjnym: Polska – Ukraina – Rosja: The image of science and scientist in the cultural and civilization aspect: Poland – Ukraine – Russia - Leszczak, Oleg (Przegląd Wschodnioeuropejski, 2020)
The purpose of the article is to show the dependence of the image on the cultural and civilizational factors determining it, i.e. from the system of stereotypes and conceptual representations that dominate in a particular society. As an example of such causation in the formation of a socially significant image, were chosen the science and the scientist, and Russia, Ukraine and Poland – as an example of cultural and civilizational space. In various cultural and civilization types science can be treated as secret or utilitarian knowledge, as sanctioned knowledge, as inspired knowledge, as a critical discourse or as a product and commodity.